2018
DOI: 10.1088/1741-2552/aa9e96
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the impact of altered axonal morphometry on the response of regenerative nervous tissue to electrical stimulation through macro-sieve electrodes

Abstract: Our work uses computational modeling to show how morphometric differences between regenerated and undisrupted tissue results in recruitment threshold discrepancies, quantifies these differences, and illustrates how large undisrupted nerve fibers close to longitudinally restricted current sources have higher recruitment thresholds compared to adjacently positioned smaller fibers while the opposite is true for large regenerated fibers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 81 publications
0
12
0
Order By: Relevance
“…This differential proliferation implies that the distance from a core channel to an average regenerated sensory axon should be less than from a peripheral channel. Previous simulations by our group (Zellmer et al, 2018) have predicted that regenerated axons' thresholds for activation are not inherently higher or lower than those of undisrupted axons, but rather depend on proximity to the stimulating lead. Effectively, thresholds for nearby regenerated axons should be lower than for naïve axons of the same caliber, while thresholds for regenerated axons that are farther away should be higher than for their naïve counterparts.…”
Section: Detection Thresholds For Single-channel Stimulus Configurationsmentioning
confidence: 79%
See 2 more Smart Citations
“…This differential proliferation implies that the distance from a core channel to an average regenerated sensory axon should be less than from a peripheral channel. Previous simulations by our group (Zellmer et al, 2018) have predicted that regenerated axons' thresholds for activation are not inherently higher or lower than those of undisrupted axons, but rather depend on proximity to the stimulating lead. Effectively, thresholds for nearby regenerated axons should be lower than for naïve axons of the same caliber, while thresholds for regenerated axons that are farther away should be higher than for their naïve counterparts.…”
Section: Detection Thresholds For Single-channel Stimulus Configurationsmentioning
confidence: 79%
“…Prior simulation work by our group (Zellmer et al, 2018) suggests that recruitment thresholds for regenerated axons are not inherently higher or lower than for undisrupted axons, but depend on their distance from the stimulating lead and the manner of stimulation. Accordingly, Zellmer et al (2018) predict that regenerated axons located near the stimulating lead should have lower thresholds than undisrupted axons and that those further away should have higher thresholds. MacEwan et al (2016) demonstrated selective recruitment of distal musculature using single-channel stimuli from an MSE implanted in the rat sciatic nerve, indicating its potential use as a chronic implant for the restoration of motor control to a paralyzed limb.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The higher threshold voltages may have multiple causes. First, newly regenerated nerve fibers crossing the MSEs’ transit zones would have smaller diameters and thinner myelin sheaths than their naïve counterparts [ 22 ]. Smaller diameter and unmyelinated fibers have previously been shown to require greater stimulation to achieve the block compared with myelinated fibers of larger diameter [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…These voltage profiles as well as the artifact at nearby electrodes on the same device were computed based on a reference stimulation current of 1 µA. Mammalian axon models implemented in NEURON (CRRSS nodal dynamics) (Chiu et al 1979, Sweeney et al 1989 representing regenerated and normal axons (Zellmer et al 2017) were used to determine the electrophysiological response of axons in a given radius around the TIME electrode or within the channel of the micro-channel device. The threshold of stimulation current to generate an action potential was determined for each axon being modeled and was used to construct recruitment curves describing the fraction of interfaced axons activated at a given stimulation amplitude.…”
Section: Methodsmentioning
confidence: 99%